Public acceptability of climate change mitigation policies: a discrete choice experiment. (1st June 2017) - Ščasný, Milan; Zvěřinová, Iva; Czajkowski, Mikolaj; Kyselá, Eva; Zagórska, Katarzyna
Abstract : The present study examines the public acceptability of the EU's future climate change mitigation policies. Using the discrete choice experiment, the authors elicit the preferences of approximately 4098 respondents from the Czech Republic, Poland, and UK for the GHG emission reduction policies that differ in four attributes: emission reduction target, burden sharing across the EU Member States, the distribution of costs within each country, and cost. The three specific reduction targets analysed correspond to the EU 2050 Roadmap and deep decarbonization policy (80% target), the climate-energy 2014 targets (40% target), and the status quo policy (20% target); each will result in a specific emission trajectory by 2050. The results reveal stark differences between the three countries. Czechs would be on average willing to pay around EUR 13 per household per month for the 40% GHG emission reductions by 2030 or EUR 17 for 80% reductions by 2050, and the citizens of the UK are willing to pay about EUR 45. Conversely, the mean willingness to pay (WTP) of Polish households for achieving more stringent targets is not statistically different from zero. The WTP for adopting policies to reach the 40% and 80% targets are not statistically different in any of the examined countries. However, it was found that the preferences in all three countries are highly heterogeneous. In addition, an insight is provided into the preferred characteristics of the future GHG emission reduction policies. Policy relevance A detailed understanding of the acceptability of climate mitigation policies among the general public is crucial for identifying the potential for improvements in their design. This study examines the public acceptability of the EU's future mitigation policies. The authors elicit preferences of respondents from three EU countries for three different emission trajectories and reduction targets through policy packages that include several options to share the burden among the EU Member States and to distribute the costs among citizens of each country. Preferences are analysed for each attribute and the willingness-to-pay values for several alternative policy packages are derived. The authors believe that understanding public acceptability can help support the successful implementation of climate mitigation policies.